MODAL SOSIAL DALAM DINAMIKA PERKEMBANGAN SENTRA INDUSTRI LOGAM WARU SIDOARJO - Witjaksono, Mit (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2010)
The new institutional economics paradigm, qualitative-interpretive paradigm, case study strategy, and narrative interviewing were applied in this research in reconstructing conceptually and theoretically how the existence and roles of social capital within the context of the dynamics of SILOW (Sentra Industri Logam Waru) development since its beginning through the development of ASPILOW (Asosiasi Pengusaha Industri Logam Waru). Four distinct social capital perspectives and MBCA (Mutually Beneficial Collective Action are used as two proxies in reconstructing the existence and roles of social capital on the dynamics of SILOW development. Based on analytical reconstruction found that structurally and cognitively the existence and roles of social capital contribute significantly to the industry development of SILOW in five phases: the embryo of blacksmith center, the blacksmith center, the metal works center (SILOW), the SILOW-Synergy I, and the SILOW-Synergy II.